Influence of mesquite derived SiO2 and Graphene reinforcement on Magnesium-Silicon alloy hybrid nanocomposites: Experimental, mechanical and wear possessions analysis - Arundeep Murugan; Suresh Vellingiri; Gunaselvi Manohar; Venkat Prasat Sridhar (Materials Research)
Lightweight materials are required in the automotive, aeronautical, defence, marine, structural, and medical industries to increase productivity. Composites are materials that combine different alloys of aluminium, magnesium, titanium, steel, copper, and other components to initiate lightweight substitutes. The goal of the current study is to create a magnesium silicon (MgSi) alloy-based hybrid nanocomposite including silicon dioxide (SiO2) nanoparticles and graphene (GR) nanoparticles at weight percentages of 0, 4, 8, and 12 using stir casting, which is the most appropriate composite production technique. Mesquite waste from agriculture is used to manufacture the various weight percentages of SiO2 nanoparticle reinforcements. Microhardness, density, porosity, tensile strength, wear, and impact strength are among the mechanical properties that are analysed. Additionally, the characteristics of X-ray diffraction (XRD), microstructure, energy-dispersive X-ray spectroscopy (EDS), and field emission scanning electron microscopy (FESEM) are used to analyze the density, microstructure, wear, CoF, and impact strength, as well as tensile specimen fracture and EDS. Comparing the MgSi/SiO2/GR hybrid nanocomposites to the Magnesium Silicon base alloy, the results indicated a significant improvement in density, tensile strength, microhardness, wear resistance, and impact strength due to the higher SiO2 and GR nano reinforcements.